Remote assessment in sport and exercise medicine (SEM): a narrative review and teleSEM solutions for and beyond the COVID-19 pandemic - Dijkstra, H. P.; Ergen, E.; Holtzhausen, L.; Beasley, I.; Alonso, J. M.; Geertsema, L.; Geertsema, C.; Nelis, S.; Huey Ngai, A. S.; Stankovic, I.; Targett, S.; Andersen, T. E. (British Journal of Sports Medicine, 2020)
Background: The COVID-19 pandemic forces sport and exercise medicine (SEM) physicians to think differently about the clinical care of patients. Many rapidly implement eHealth and telemedicine solutions specific to SEM without guidance on how best to provide these services.